Improving 21st Century Competencies: Implementation of Problem- and Project-Based Digital Maze Games in Early Childhood - Sutama, I Wayan; Astuti, Wuri; Pramono (Universitas Pendidikan Ganesha, 2024)
21st century competencies are very important to develop. Developments continue to occur over time, especially in the fields of technology and economics. However, the reality on the ground shows that 90% of IT use in education is only to access information and videos shown to children. This makes communication only go in one direction and does not stimulate children's critical thinking skills. This research aims to produce a design and analyze the validity of digital maze game media to stimulate 21st century skills in children aged 5-6 years. This research is included in the type of development research using the ADDIE model. The subjects in this study were 30 children with 2 material expert validators and 2 media expert validators. The data collection technique uses a questionnaire. The data that has been collected is then analyzed using descriptive quantitative analysis. The results of the material expert validity test obtained a score of 90% (very feasible), the media expert validation test 97% (very feasible), the results of individual trials obtained a total average of 77.5% (feasible). It can be concluded that the novelty of the digital maze game media is suitable for use in learning to stimulate the 21st century skills of children aged 5-6 years. The implication of this research is that it can attract children's enthusiasm for learning. In this way, children can have collaboration skills, digital literacy, and improve critical thinking skills through problem solving to discover new vocabulary.